Concept of Educational Quality Management from General and Islamic Perspectives - Alimin Alimin; Rukyatun Ulya; M. Sobry (Jurnal Ilmiah Profesi Pendidikan, 2025)
Educational Quality Management (EQM) represents a vital and systematic endeavor to achieve institutional excellence and ensure stakeholder satisfaction. This article undertakes a focused examination of the EQM concept from both general and Islamic perspectives, aiming to analyze and compare their fundamental definitions, targets, and core principles. The study employs a literature review method, relying entirely on the analysis of texts and documents, including academic books, Islamic educational management literature, government regulations, and secondary empirical data such as PISA survey results. The analysis was conducted using qualitative content analysis and thematic integration to construct a comprehensive understanding. The findings show that general EQM focuses on effectiveness, efficiency, stakeholder involvement, continuous improvement, and data-driven decision-making. The Islamic perspective enriches this by integrating spiritual values like faith (iman), sincerity (ikhlas), diligence (itqan), excellence (ihsan), and accountability. Consequently, educational quality is measured holistically, encompassing both academic achievement and the successful cultivation of noble character and social well-being. The integration of these modern principles with Islamic values is presented as a strategic foundation for strengthening education quality in Indonesia, particularly in addressing persistent challenges like low scores in literacy, numeracy, and creative thinking skills among students.